Description of Titanoeca deltshevi sp. n. from Bulgaria with faunistic notes on related species in the Balkans (Araneae, Titanoecidae) - Naumova, Maria (Zootaxa, 2019)
Titanoeca deltshevi sp. n. is described and illustrated from Bulgaria. It appears closely related to T. praefica (Simon, 1870), T. spominima (Taczanowski, 1866) and partially (males only) to T. flavicoma L. Koch, 1872. A faunistic synopsis of the genus Titanoeca Thorell, 1870 in Bulgaria is also presented that is based on new field data and a review of the published literature. Titanoeca flavicoma is newly recorded for Bulgaria and T. turkmenia Wunderlich, 1995 is new for Bulgaria and Albania. Titanoeca incerta (Nosek, 1905) is removed from the Bulgarian, and therefore from the European spider checklists. The possible division of the European members of Titanoeca into three groups based on differences in copulatory and somatic traits is discussed.